Utilisation et regénération des écailles de cacao pour la récupération du plomb dans les solutions acides. Issue 1 (1st January 2003) - Meunier, Nathalie; Haberman, Michael; Blais, Jean-Francois; Tyagi, Rajeshwar Dayal
Abstract : Cocoa shells, a by-product of the food industry, is a promising adsorbent for the treatment of acid metal loaded wastewaters, particularly for lead removal. Elution tests carried out using different concentrations of hydrochloric acid have shown that a good portion can be eluted using a short contact time (approximately 10 min) and a diluted acid solution (0.51.0 M). The use of a more concentrated acid solution causes significant mineralization of the adsorbent and does not allow to improve the elution yield. Repeated adsorptionelution cycles have shown that cocoa shells can be reused for many times. However, their lead adsorption capacity progressively decreases from 19.3 mg Pb/g during the 1st cycle to 4.8 mg Pb/g during the 10th cycle. Finally, the use of successive adsorptionelution cycles is only interesting, from an economical point of view, in the case where the acid solution is used for many elution steps. Key words : adsorption, elution, lead, cocoa shells, effluent, acid.